STRETCH FORMING USING HEATED DIE - COSMIN CONSTANTIN GRIGORAȘ; BOGDAN CHIRIȚĂ; VALENTIN ZICHIL; EUGEN HERGHELEGIU; CĂTĂLIN TÂMPU; VLAD CIUBOTARIU (Journal of Engineering Studies and Research)
The stretch forming process implies stretching and drawing into shape a sheet of material onto a die. This method is used, among other sectors, in the construction of aeroplane fuselage, as significant, complex parts can be obtained in one piece. In essence, stretch forming implies working with materials that have medium to high spring back effects, such as aluminium or magnesium alloys. Different approaches are used in manufacturing due to this phenomenon, ranging from incremental processes to multipoint dies. Another critical aspect of this process is to know how the material behaves under severe plastic deformation, as different alloys require different approaches that vary from step by step forming to in-process chemical treatments to manual pounding the metal sheet. However, all these alloys have in common that, when heated, their machinability properties improve. In this experimental study, a heated die approach was taken into consideration. 6x60 mm 100W heating elements along with temperature sensors were fitted into the die. The USB/OC326009 metal sheet is in direct contact with the die, thus assuring the heat transfer, as the temperatures reach 200 °C. The die temperature is software controlled so that maximum temperature and thermal inertia could be controlled with ease. The data indicate that this method offers significantly improved results compared to a normal room-temperature process.